Hondo & Fabian - McCarty, Peter (New York Henry Holt, 2002)
Hondo the dog gets to go to the beach and play with his friend Fred, while Fabian the cat spends the day at home.
Keywords: Dogs -- Juvenile fiction; Cats -- Juvenile fiction; Dogs -- Fiction; Cats -- Fiction; Pets -- Fiction